China-Pakistan Economic Corridor: Analytical overview on Socio-Cultural Romance between China and Pakistan - Muhammad Asif; Majid Ali; Abdoulaye M’Begniga; Zhou Guoqing; Liu Yang; Muhammad Hashim (RIRAI Publisher, 2021)
China Pakistan Economic Corridor (CPEC) is an important Belt and Road Initiative (BRI) project that integrates many countries. The CPEC project will play a vital role to make more strong relationship between China and Pakistan. CPEC project will enhance cooperation between Pakistan and China in field of socio-cultural and regional Bilateral Cooperation and exchange. Despite growth between two countries in the economic and trade field, there is a vital area to explore the cultural exchange, cooperation, and communication needed to improve from both sides. In this theoretical study method, the data has been obtained from primary and secondary sources. The primary sources consisted of books, official databases of China and Pakistan, MoU signed b/w both countries, etc., as the secondary sources consisted of research papers, newspapers, journals, online databases, etc. This paper has an analytical overview of the time value and general cultural and artistic exchanges between China and Pakistan. Further, the paper discussed the relationship between literature, art, and economics. In this paper, researchers have also examined the significant role of people-to-people contact for socio-cultural exchange and cooperation between China and Pakistan.